2014
DOI: 10.1186/1471-2458-14-217
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination coverage of children aged 12-23 months in Gaziantep, Turkey: comparative results of two studies carried out by lot quality technique: what changed after family medicine?

Abstract: BackgroundHealth care systems in many countries are changing for a variety of reasons. Monitoring of community-based services, especially vaccination coverage, is important during transition periods to ensure program effectiveness. In 2005, Turkey began a transformation from a “socialization of health services” system to a “family medicine” system. The family medicine system was implemented in the city of Gaziantep, in December, 2010.MethodsTwo descriptive, cross-sectional studies were conducted in Gaziantep c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…We think that this may be attributed to the lack of easy access to health care in rural areas. It is possible that the rate of booster vaccination is lower because, over time, physicians and individuals lose interest in maintaining vaccine coverage in rural areas of Turkey (20). In this study it was observed that immunity to tetanus increased with education level, which was compatible with another study from Turkey (21).…”
Section: Discussionsupporting
confidence: 90%
“…We think that this may be attributed to the lack of easy access to health care in rural areas. It is possible that the rate of booster vaccination is lower because, over time, physicians and individuals lose interest in maintaining vaccine coverage in rural areas of Turkey (20). In this study it was observed that immunity to tetanus increased with education level, which was compatible with another study from Turkey (21).…”
Section: Discussionsupporting
confidence: 90%
“…The poor literacy rate among these parents shows their casual attitude regarding their child's health. Furthermore, health education should also notify health workers about records and familial concerns about vaccination and keeping vaccination cards [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…We think that both physicians and women lose interest in maintaining vaccine coverage. The review of two studies assessing vaccinations of women of childbearing age showed fewer cases of neonatal tetanus when two or three doses were applied [26]. According to a study conducted in Pakistan, 87% of the women recalled receiving 2 doses of TT [27].…”
Section: Discussionmentioning
confidence: 99%